Patient-Reported Outcome Measures After Liver Resection: A Prospective Single-Center Analysis of Patient-Reported Outcomes and Predictors of Recovery - Matteo Colangelo; Marcello Di Martino; Teresa Gatto; Paolo Baroffio; Matteo Donadon (Cancers, 2026)
Background: Traditional outcome assessment after liver surgery mainly relies on perioperative morbidity and mortality. However, these parameters fail to capture the multidimensional recovery experienced by patients after hepatic resection. This study aimed to evaluate changes in quality of life (QoL) between the preoperative and three-month postoperative assessments using Patient-Reported Outcome Measures (PROMs) and to identify factors associated with impaired postoperative recovery. Methods: A prospective observational study was conducted including 71 consecutive patients undergoing liver resection at a tertiary hepatobiliary referral center between May 2024 and May 2025. QoL was assessed preoperatively and three months after surgery using the EORTC QLQ-C30 and QLQ-LMC21 questionnaires. PROMs were correlated with demographic, clinical, operative, and postoperative variables. Univariable and multivariable analyses were performed to identify factors associated with worse postoperative QoL. Results: Significant improvements in postoperative QoL were observed at three months compared with baseline in both the QLQ-C30 and QLQ-LMC21 questionnaires (both p < 0.001). Psychological domains also significantly improved after surgery. Patients with ASA scores ≥ 3 (p = 0.044) and those requiring intraoperative blood transfusion (p = 0.011) reported significantly worse postoperative quality-of-life scores. On multivariable regression analysis, Grade B bile leak was associated with impaired postoperative QLQ-C30 outcomes (95% CI 0.75–23.81; p = 0.038). Conclusions: Liver resection was associated with improvement in patient-reported QoL three months after surgery. PROMs provide clinically relevant information beyond conventional surgical metrics and may help identify patients requiring tailored perioperative support. The integration of PROMs into liver surgery pathways may contribute to the development of a more patient-centered model of surgical care.